1997
DOI: 10.1159/000218039
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Hepatoma Cells by Alpha-Fetoprotein

Abstract: We have investigated the effects of purified human α-fetoprotein (AFP) on the growth of the human hepatocarcinoma cells HepG2 in culture. Cancer-derived AFP (cAFP), isolated from the culture medium of AFP-secreting HepG2 cells and embryonal AFP (eAFP), isolated from human cord serum, were used for these studies. Both AFP preparations studied were shown to induce strong dose-dependent inhibition of HepG2 cell proliferation and complete growth arrest at high protein concentrations (more than 0.1 mg/ml). To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Prior to the addition of reagents, the culture medium from the adherent cells was removed by an automatic pipette, and 0.18 ml of fresh medium with or without FCS was added to the wells and left for 2 h. Thereafter, serially diluted AFP or human serum albumin (HSA, Sigma) in 0.02 ml of phosphate-buffered saline (PBS) was introduced to the wells for 24 h. For the last 4 h of incubation, 1 ÌCi of [ 3 H]-thymidine (1 Ci/mmol) was added to each well. Experimental data were expressed as a percentage of [ 3 H]-thymidine incorporation relative to the medium control [39,42].…”
Section: Cell Growth Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the addition of reagents, the culture medium from the adherent cells was removed by an automatic pipette, and 0.18 ml of fresh medium with or without FCS was added to the wells and left for 2 h. Thereafter, serially diluted AFP or human serum albumin (HSA, Sigma) in 0.02 ml of phosphate-buffered saline (PBS) was introduced to the wells for 24 h. For the last 4 h of incubation, 1 ÌCi of [ 3 H]-thymidine (1 Ci/mmol) was added to each well. Experimental data were expressed as a percentage of [ 3 H]-thymidine incorporation relative to the medium control [39,42].…”
Section: Cell Growth Assaymentioning
confidence: 99%
“…On the contrary, growth-suppressive properties of pure AFP and of the AFP/estradiol reaction product were conclusively demonstrated in vivo and in vitro for both human and rat breast tumors [34][35][36][37][38]. Our recent data showed that human embryonal AFP, derived from human cord serum, and cancerassociated AFP, purified from the culture medium of AFP-secreting human hepatoma cells, can induce apoptotic cell death in sensi- Dudich/Semenkova/Gorbatova/ Dudich/Khromykh/Tatulov/Grechko/ Sukhikh tive HepG2 cells in a dose-dependent manner [39].…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism independent from the apoptosis-inducing effects is the stimulation of anti-tumor immune response. AFP enhances the dendritic-cell-mediated immune reaction of T-lymphocytes against tumor cells (31,32). It is intriguing that AFP isolated from human cord serum has been shown to inhibit the growth of human hepatocarcinoma cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…AFP might also function as an apoptotic factor. (15)(16)(17)(18)(19) However, the molecular background of HCC associated with increased AFP levels, the mechanisms responsible for the recurrence of HCC are presently unclear.Gene expression analysis by cDNA microarray offers a systematic approach to acquire comprehensive information regarding gene transcription profiles. It is now possible to perform a large-scale expression survey to identify candidate target genes and to develop a novel molecular-targeted therapy for HCC.…”
mentioning
confidence: 99%
“…AFP might also function as an apoptotic factor. (15)(16)(17)(18)(19) However, the molecular background of HCC associated with increased AFP levels, the mechanisms responsible for the recurrence of HCC are presently unclear.…”
mentioning
confidence: 99%